Utilisation possibility of Enterococcus faecalis isolates from neonate's faeces for production of fermented sausages as starter cultures. (22nd May 2017) - Ba, Hoa Van; Seo, Hyun‐Woo; Cho, Soo‐Hyun; Kim, Yoon‐Seok; Kim, Jin‐Hyoung; Park, Beom‐Young; Kim, Hyun‐Wook; Ham, Jun‐Sang; Seong, Pil‐Nam
Summary: This study aimed at assessing the utilisation possibility of Enterococcus faecalis as starter cultures for production of fermented sausages. The E. faecalis isolates isolated from faeces samples of 5‐day‐old healthy newborn babies, identified by 16SrDNA sequencing and free from virulence determinants as proven by genomic sequencing, were used for fermented sausages production as starter culture. Six treatments (four inoculated with four different E. faecalis isolates, one with commercial starter culture and one control) were prepared. The inoculation with E. faecalis showed a stronger acidification compared with the control. The treatments with E. faecalis showed significantly higher flavour and acceptability scores in comparison with the control or commercial starter culture. Both of commercial starter culture and E. faecalis were positive with tyramine. Apart from the amine production, the inoculation with E. faecalis generally improved the acidifying activity and flavour of the products, suggesting their application potentials in fermented sausages production as starter cultures. Abstract : Procedures of isolation, identification and utilization of Enterococcus faecalis isolates for production of fermented sausages.